From Dynamic Modeling to Experimentation of Induction Motor Powered by Doubly-Fed Induction Generator by Passivity-Based Control - Becherif, M.; Bensadeq, A.; Mendes, E.; Henni, A.; Lefley, P.; Ayad, M.Y (IntechOpen, 2011)
None